KEPENTINGAN INDONESIA TIDAK MERATIFIKASI FRAMEWORK CONVENTION ON TOBACCO CONTROL (FCTC) - Nofri Yuska; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
FCTC is an international regulation for tobacco control in the world, convention for tobacco control the world was born from worries of the World Health Organisation (WHO ) about the risks and dangers posed by the effect of negative tobacco (cigarettes) against the world public health. Through smoke by the active smokers and accepted by the passive smokers. FCTC approved as international law in June 2005 by the World Health Assembly (WHA) and until January 2014 has ratified by 185 members of WHO.Indonesia is the one of the 8 countrys that were not ratify FCTC, Indonesian government considers that ratification of FCTC not yet necessary important by Indonesia itself. It is caused by rather negative against the government of Indonesia to the impact of economic stability in the country. Tobacco sector is one of the source of revenue for state coffers sizable, besides tobacco industry is also capable of creating jobs for millions of farmers and cigarette factory workers. Above that some consideration, the Indonesian government has not ratified the results of the world convention on tobacco control.Keywords : Tobacco, , Ratification, Indonesia, Cigar